Technical Vocational Education and Training Students’ Migration Between Programmes - Gomba, Georgina Kedibone; Malale, Matthews Matome (International Journal of Educational Development in Africa, 2025)
Technical Vocational Education and Training (TVET) colleges constitute a relatively new sector of South Africa’s education system. This sector offers different programmes, including three-year National Certification Vocational (NC(V)) programmes and Report 191 or National Accredited Technical Education Diploma (NATED) programmes. The enrolment at TVET colleges has risen dramatically since the recapitalisation of these colleges. However, students’ inclination to shift to Report 191 (NATED) courses during or after NC(V) programmes tarnishes this growth. This has an impact on the effective operations of TVET colleges and may render NC(V) programmes ineffective. This study investigated the causes of student migration between programmes so as to suggest improvement measures. A qualitative case study was conducted on a single TVET institution in Limpopo, South Africa. Purposive sampling was used, and face-to-face interviews were conducted with 10 students and four lecturers. The students’ registration records, the departmental TVET policy (Post-School Education and Training), and the college admission policy were reviewed to supplement the interview data. The interviews were audio-recorded and observations were documented to ensure the accuracy of data. The data was interpreted using the Theory of Planned Behaviour. The findings revealed that students switched programmes because companies undervalue NC(V) programmes, which might impair their career prospects. This relocation also impacts on resource allocation owing to inaccurate enrolment statistics. Based on the study’s findings, TVET colleges and the Department of Higher Education and Training (DHET) should promote NC(V) programmes more. The DHET should inform prospective employers about different programmes offered by TVET institutions, to enhance their prominence.